PENGARUH LATIHAN ONE-ON-ONE SHADOW TAG TERHADAP KELINCAHAN PADA ATLET SEPAKBOLA SSB CHEVRON PEKANBARU - Ferdianto, Rudi; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the observations that researchers do at SSB Chefron Pekanbaru has a number of disadvantages, including the speed, durability, and agility of the athletes of the SSB Chefron Pekanbaru, but the most can be seen in terms of the player Agility, it can be seen when they are training or during the league, the SSB Chefron athletes are not manoeuvrable in changing directions quickly. That makes the author a discussion about maneuverability. The purpose of this research is to know the influence of one-on-one Shadow tag exercises on the agility of the football athletes in the SSB Chefron Pekanbaru. The population in this study is SSB Chefron Pekanbaru which came down to 18 people. Sampling uses a total sampling technique based on population counting. The instrument in this study are Shutlerun test. The data obtained in the ananlysis using t-test. Based on the research carried out to the athletes of SSB Chefron Pekanbaru, taken from the results of the first Test skill dribbled, then given drble exercises and use . T test results show Thitung of 3.500 with this 1.71 then received, at Alpha level (0.05).Key Words: One-on-one Shadow tag, Agility